2013
DOI: 10.1007/s10695-013-9853-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sex and season in haematological parameters and cellular composition of spleen and head kidney of pejerrey (Odontesthes bonariensis)

Abstract: Phylogenetic diversity in fish determines high interspecific variability in morphology as well as in physiological parameters. Moreover, several haematological variables and the organ composition of haemolymphopoietic sites may vary according to sex or season. The aim of this study was to establish the haematological parameters and the cellular composition of haemolymphopoietic organs in Odontesthes bonariensis, a commercially valuable fish species in Argentina, and also to determine gender or seasonal variati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…In this study, WBC counts of mackerels were lower in April than those measured during August. A similar response was found in tench, sea bass, spirlin, pejerrey and Indian hill trout (Collazos et al 1998, Pascoli et al 2011, Kohanestani et al 2013, Vigliano et al 2014, Sharma et al 2017. It has been suggested that ambient changes along the year, such as photoperiod and temperature, may induce changes in the immune system.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…In this study, WBC counts of mackerels were lower in April than those measured during August. A similar response was found in tench, sea bass, spirlin, pejerrey and Indian hill trout (Collazos et al 1998, Pascoli et al 2011, Kohanestani et al 2013, Vigliano et al 2014, Sharma et al 2017. It has been suggested that ambient changes along the year, such as photoperiod and temperature, may induce changes in the immune system.…”
Section: Discussionsupporting
confidence: 54%
“…The effects of seasonality during April and August on the mackerel were observed for blood parameters such as MCH, WBC count, total protein, globulin, glucose, and triglycerides. Seasonal variation in hematological parameters has been found in tench (Tinca tinca), sea bass (Dicentrarchus labrax), Indian carp, spirlin, pejerrey (Odontesthes bonariensis), snow trout (Schizothorax plagiostomusto), and Indian hill (Collazos et al 1998, Pascoli et al 2011, Pradhan et al 2012, Kohanestani et al 2013, Vigliano et al 2014, Sheikh & Ahmed 2016, Sharma et al 2017. Variations in hematologic parameters are due to seasonal water temperature and dissolved oxygen variations (Kohanestani et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In this study thrombocyte count showed the maximum in winter and minimum in summer, similarly as WBC and activity of phagocytes (NBT). Similarly maximum thrombocyte count was also observed by Gupta et al 2013and Langer et al (2013), contrary to the findings by Orun et al (2003) and Vigliano et al (2014). Stosik et al (2019) noted that thrombocytes in fish display strong defence potential which is expressed in their phagocytic activity and ability to neutralise and degrade the bacteria absorbed.…”
Section: Discussionmentioning
confidence: 69%
“…There is little information about seasonal variation in thrombocyte count in fish, and the data obtained by various authors are contradictory: increase in summer was reported by Orun et al (2003) and Vigliano et al (2014), Jeronimo et al (2011), Gupta et al (2013, while Langer et al (2013) observed maximum thrombocyte abundance in winter. Santos et al (2009) and Seriani et al (2013) found no significant seasonrelated alterations.…”
Section: Introductionmentioning
confidence: 97%
“…Though many studies do not identify significant sex differences of hemoglobin levels in fish 37 , Falahatkar et al 38 discovered decreased hemoglobin concentrations and hematological changes in juvenile Acipenser stellatus that were treated with estradiol for 7-9 months. They predict estradiol may have an inhibitory effect on erythropoiesis (the production of red blood cells).…”
Section: Resultsmentioning
confidence: 99%